Pluralism and Identity in the Indonesian-Malay World: The Isrā’ Mi’rāj as a token of both - Dick van der Meij (Studia Islamika, 2004)
This article would like to have o look at one particular piece of literature, the story of Isra' Mi'raj, to explore whether it is possible to say something about identity and plurality in the Indonesian-Malay world. It will propose that the story of the Isra' Mi'raj is a token of both the plural aspect of the Indonesian-Malay world as well as constituting a vital element of the shared identity of the inhabitants of this Southeast Asian region. It will do so by presenting thirteen examples of Isra' Mi'raj material available in, or originating from, the Indonesian-Malay world and present some attractive examples of the pluralism found in the stories. Subsequently it will propose that the Isra' Mi'raj functions as token of identity in this area.DOI: 10.15408/sdi.v11i3.595